Predicting Customer Orientation Using the Theory of Planned Behavior: A Case of the Iranian Gas Industry (Nexo Revista Científica, 2023)
The purpose of this research was to predict customer orientation in the Iranian gas industry using the theory of planned behavior (TBH). The population of this quantitative survey con-sisted of gas industry employees, and a sample size of 384 was calculated using Cochran’s formula for infinite population. Data was collected using a questionnaire. The content validity of the instrument was verified by a panel of experts, and its construct validity and reliability were confirmed through confirmatory factor analysis and Cronbach’s alpha. Data was ana-lyzed using confirmatory factor analysis and structural equations modeling. The results showed that discipline, knowledge, moral norms, subjective norms, and perceived behavioral control have a significant positive effect on customer orientation. Moreover, planned behavior was significantly associated with customer orientation in the gas industry. Therefore, TBH can be used for predicting customer orientation in the gas industry.